Ecology and taxonomy of peritrichous ciliates (Ciliophora, peritrichia) in different ambients - Peštová, Dana, 1980- (2007)
Author: Dana Peštová Title of the dissertation work (Czech): Ekologie a taxonomie peritrichů (Ciliophora, peritrichia) v různých prostředích. Title of the dissertation work (English): Ecology and taxonomy of peritrichous ciliates (Ciliophora, peritrichia) in different ambients. Field of study: Biology Study programm: Hydrobiology Advisors: ing. Miroslav Macek, CSc., doc. RNDr. Jan Helešic, Ph.D. Year of defence: 2007 Annotation Diversity, dynamics and taxonomy of ciliates (especially, peritrichs) were studied by means of protargol staining. Grazing on autotrophic picoplankton were estimated under in situ conditions using Fluorescently labelled bacteria in saline monomictic lakes Alchichica and Atexcac, state Puebla, Mexico and Valle de Bravo reservoir, state of Mexico, Mexico